Orbital outcomes after orbit-sparing surgery and free flap reconstruction. (November 2019) - Philips, Ramez; Topf, Michael C.; Graf, Alexander; Krein, Howard; Heffelfinger, Ryan; Luginbuhl, Adam; Curry, Joseph
Highlights: Spared orbit was functional in 98% of patients. Postoperative orbital sequelae occurred in 65.3% of patients. Twenty-one patients underwent 35 operations for orbital sequalae. Radiation therapy and extent of resection correlated with impairment in functional orbit. Abstract: Objective: To identify functional outcome and orbital complication rate of the preserved orbit and to identify predictors of orbital impairment in periorbital free flap reconstruction. Materials and methods: A retrospective review was conducted on patients undergoing orbit-sparing surgery with periorbital free flap reconstruction at a tertiary institution from 2006 to 2017. Orbital complication rate and orbital functional outcomes were analyzed. A univariable and multivariable logistic regression analysis was used to assess predictors of functional outcome. Results: Forty-nine patients met inclusion criteria. Ninety-eight percent of patients maintained a functional eye post-operatively. Most periorbital free flaps, 37 (75.5%), were performed following oncologic resection. Overall orbital function was graded as functional without impairment in 29 (59.2%) patients, functional with impairment in 19 (38.8%) patients, and nonfunctional in 1 (2.0%) patient. Postoperative orbital sequelae occurred in 32 (65.3%) patients. Twenty-one (42.9%) patients underwent 35 revision operations for late orbital sequelae. Extent of resection (OR, 5.93; CI 95%, 1.05–33.4; p = 0.044) and adjuvant RT (OR, 4.69; CI 95% 1.18–18.6; p = 0.028) significantly correlated with impairment in a functional orbit on multivariable analysis. Conclusion: Orbit-sparing surgery with periorbital free flap reconstruction carries a significant risk of a variety of orbital sequelae, most commonly ectropion, requiring surgical intervention. However, most patients maintain a functional eye. The need for delayed exenteration/enucleation is low and is primarily limited to cancer recurrence. Significant predictors of complications include extent of resection and adjuvant radiation therapy.